Impact of Creativity In Relation to Academic Achievement of IX Standard Students in and Around Tiruvallur District - Jennifer, Deepika; Selvakumar, Y. Stanly (Journal of Advanced Research in English & Education; Vol 8 No 2 (2023): Journal of Advanced Research in English & Education, 2023)
The ability to come up with or uncover original ideas is known as creativity. It might also entail changing or rebuilding the original concept. The ability of the human mind to shift relations and produce new correlates in order to create new contents is known as creativity. The result of education is academic achievement, or (academic) performance, which measures how well a student, instructor, or institution has met its learning objectives. The data collected the data from 300 samples from 3 different types of schools. The data was quantified as per the scoring procedure and analyzed using suitable statistical computations like mean, standard deviation, correlation, regression and stepwise regression analysis. The interpretation of the problem is discussed in this chapter on the basis of hypothesis framed.